A multidisciplinary approach to operationalizing financial toxicity interventions: The MSK Affordability Working Group. Issue 28 (1st October 2022) - Aviki, Emeline Mariam; Chino, Fumiko; Gany, Francesca; Caramore, Amy; Doyle, Stephanie; Liebhaber, Allison; Newman, Tiffanny; Sokolowski, Stefania; Thom, Bridgette
Abstract : 2 Background: The financial toxicity (FT) of cancer is a concern for the healthcare system. Rising costs and increased cost-sharing result in high levels of financial burden, with negative implications for treatment adherence, quality of life, and financial well-being. As FT interventions must consider the interdependent systems of barriers patients face, this project highlights efforts toward developing and testing hospital-based FT interventions through the creation of the Memorial Sloan Kettering (MSK) Affordability Working Group. Methods: An interdisciplinary task force aimed to 1) characterize FT among patients receiving treatment at MSK; 2) identify areas for systemic change. Members included physicians, nurses, and social workers, and representatives from patient billing/financial services, health services research, and hospital administration and strategy. The team first conducted a review of medical records (2016 – 2018) to determine FT incidence and current practices for financial assistance uptake. Absent a formal FT screening, proxy measures defined FT as having bill payment issues, applying for financial assistance, or expressing financial concerns to Social Work, and we analyzed the percent of each category referred for assistance. Post-analysis program processes are also described. Results: Of 89, 283 records reviewed, 22, 187 (25%) patients experienced FT. Of 14, 178 patients with payment issues, only 22% had been referred for financial assistance. As such, streamlining the assistance referral process became a priority, leading to the creation of an FT order set for providers to make direct referrals. From 3/2021-2/2022, 843 orders were placed, with $836, 000 in co-pay assistance and $13, 500 in essential needs assistance linked to the order set. The task force then met with hospital leadership to formally expand into an institutional working group, with organizational buy-in demonstrated through increased staffing and monetary support of patient-level pilot interventions. Stakeholders were engaged through presentations at departmental grand rounds and to individual disease teams. Operational and research efforts are now focused on systematic FT screening of patients, including validating a screening tool, developing nurse-led staff and patient education, assessing stakeholder feedback, and determining an appropriate screening cadence and workflow by disease type. Conclusions: With at least 25% of patients at MSK experiencing financial difficulties related to cancer treatment, it was, and remains, vital to develop systems-based interventions to proactively assess FT risk and refer to tangible resources. Planned future work includes implementation of universal FT screening with reflex referral to financial assistance, testing patient-level educational interventions, and developing policy/advocacy recommendations.